Antibiotic Use Patterns in Obstetric and Gynecological Surgery Patients: A Quantitative Descriptive Study Using ATC/DDD and DU90% Methods - Maryamah Azzahra; Difa Intannia; Dita Ayulia Dwi Sandi; Reni Yustiati Saksono; Revina Aditya Yosita; Herningtyas Nautika Lingga (Journal of Pharmascience, 2026)
Surgical site infections (SSIs) are common postoperative complications in obstetric and gynecological surgery, with incidence rates up to 20% in cesarean sections. Antibiotics are the primary strategy for SSI prevention; however, antibiotic utilization patterns in this surgical setting remain poorly characterized locally. This study describes the antibiotic use profile, AWaRe classification, DDD/100 patient-days values, and DU90% segment among obstetric and gynecological surgery patients at Ulin Regional General Hospital, Banjarmasin, in 2024. A retrospective, non-experimental quantitative descriptive design was employed. Of 313 medical records reviewed, 137 met the inclusion criteria. A total of 173 antibiotic prescriptions were identified. Ceftriaxone was the most frequently used antibiotic (61.84%), with cephalosporins predominating (91.91%) and parenteral administration in 75.72% of cases. Based on the WHO AWaRe 2022 classification, 85.55% of antibiotics were in the Watch group and 13.29% in the Access group; no Reserve antibiotics were used. Ceftriaxone had the highest DDD/100 patient-days (33.74). Ceftriaxone and cefixime comprised the DU90% segment. These findings highlight a predominance of Watch-group antibiotics and support the need for targeted stewardship interventions